A Study On Language Learning Strategies Among Male And Female Malaysian University Students - Jooneghani, Raziel-I Bahraminezhad (2015)
Research on strategy has proven the significance and usefulness of language learning strategies (LLS) for ESL students. The aim of this research is to examine any significant differences among male and female university students in three universities in Malaysia regarding the use of strategies. In this research, 250 male and female undergraduate students who studied in public universities are involved. A quantitative method is used in this study. Descriptive analysis is conducted in order to identify each strategy range of use (high, medium, low) and also to classify the most and the least ten frequently used strategies in general. Also, independent t-test analysis is utilized to identify the differences between male and female students towards strategies ofLLS. Data analysis shows that except social strategies, there are significant differences between male and female students in terms of using the other five language learning strategies; namely, memory, cognitive, compensation, metacognitive and affective.